Synthesis of a Magnetic Carnation-like Hydroxyapatite/Basic Calcium Carbonate Nanocomposite and Its Adsorption Behaviors for Lead Ions in Water - Haifeng Guo; Siru Hu; Zongli Wang; Yutong Li; Xinshuang Guo; Ziling He; Wenbin Wang; Jun Feng; Kangyun Yang; Hong Zheng (Molecules, 2022)
Calcium-enriched compounds have great potential in the treatment of heavy-metal contaminated wastewater. Preparing stable basic calcium carbonate (BCC), which is a calcium-enriched compound, and applying it in practice is a great challenge. This work investigated the formation process of hierarchical hydroxyapatite (HAP)/BCC nanocomposites and their adsorption behaviors regarding lead ions (Pb2+). The morphology of the HAP/BCC nanocomposite was controlled by the addition of monododecyl phosphate (MDP). The carnation-like HAP/BCC nanocomposite was achieved with the addition of 30 g of MDP. The carnation-like HAP/BCC nanocomposite had a high Pb2+ adsorption capacity of 860 mg g−1. The pseudo-second-order and Freundlich model simulation results indicated that the adsorptions of Pb2+ on the nanocomposites belonged to the chemisorption and multilayer adsorption processes. The main effective adsorption components for the nanocomposites were calcium-enriched HAP and BCC. Through the Ca2+ ions exchanging with Pb2+, the HAP and BCC phases were converted to hydroxyl-pyromorphite (Pb-HAP) and hydrocerussite (Pb3(CO3)2(OH)2), respectively. The carnation-like HAP/BCC nanocomposite has great potential in the treatment of heavy metal ions. This facile method provides a new method for preparing a stable HAP/BCC nanocomposite and applying it in practice.